2009
DOI: 10.1037/a0012567
|View full text |Cite
|
Sign up to set email alerts
|

The moderating effects of personal reputation on accountability-strain relationships.

Abstract: Although felt accountability has predicted positive outcomes in some studies, it has demonstrated anxiety-provoking properties in others. This inconsistency has led researchers to search for moderating variables that explain why felt accountability promotes or impedes favorable outcomes. Building on these studies, the authors examine the moderating effects of personal reputation on the felt accountability-strain relationship. As hypothesized, the results indicate that a positive personal reputation ameliorated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 89 publications
2
39
0
3
Order By: Relevance
“…Specifically, the impact of ethical leadership on the EOR is amplified for leaders that are also evaluated as high performers. Personal reputation is an important asset because it reduces uncertainty concerning future behavior by signaling that the individual is trustworthy and has the necessary abilities to deal with workplace demands (Laird et al, 2009). This interaction effect is aligned with Hochwarter et al's (2007) claim that in order to fully understand how influence processes take place, one needs to examine the role of personal reputation.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Specifically, the impact of ethical leadership on the EOR is amplified for leaders that are also evaluated as high performers. Personal reputation is an important asset because it reduces uncertainty concerning future behavior by signaling that the individual is trustworthy and has the necessary abilities to deal with workplace demands (Laird et al, 2009). This interaction effect is aligned with Hochwarter et al's (2007) claim that in order to fully understand how influence processes take place, one needs to examine the role of personal reputation.…”
Section: Discussionmentioning
confidence: 90%
“…For example, Laird, Perryman, Hochwarter, Ferris and Zinko (2009) found that an increase in felt accountability in the workplace presented quite different results, depending on the person's reputation. Similarly, Hochwarter et al (2007) found that the relationship between political behavior and several outcomes (uncertainty, exhaustion and performance) varied significantly depending on the levels of personal reputation.…”
Section: Ethical Leadership and The Employee-organization Relationshipmentioning
confidence: 99%
“…The majority of examinations of reputation explore the potential benefits of holding a positive reputation (e.g., Laird et al, 2008). In recognition of the relevance of such research, we focus on the existing empirical as well as theoretical findings regarding outcomes.…”
Section: A Model Of Personal Reputation Inmentioning
confidence: 99%
“…Over the last decade, a body of knowledge has developed that examines why individuals and organizations may wish to create positive reputations (e.g., Hall, Zinko, Perryman, & Ferris, 2009;Laird, Perryman, Hochwarter, Ferris, & Zinko, 2008;Laird, Zboja, Martinez, & Ferris, 2013;Zinko, 2013;Zinko, Gentry, Hall, & Grant, 2012). Research has suggested that the outcomes of possessing a positive reputation have such valuable benefits, that both organizations as well as individuals often devote a substantial amount of resources to the matter (Ferris, Blass, Douglas, Kolodinsky, & Treadway, 2003;Gray & Balmer, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Today, job stress is one of the most important issues in social life and it is considered as a serious threat for workforce health in all of the world such that International Labor Organization explicitly considered job stress is as the most known threatening cause of workers' health [4]. Stress is one of the most prevalent concepts in psychological and social research areas [5].…”
Section: Introductionmentioning
confidence: 99%